Studi Empiris: Pengaruh Firm Size, Current Ratio, dan Total Asset Turnover Terhadap Profitabilitas Melalui Return on Equity - Wenny Anggeresia Ginting; Siti Aisyah Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study examines the effect of Firm Size, Current Ratio, and Total asset turnover on profitability proxied by Return On Equity. The population used in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018, totaling 19 companies. The sample used as many as 50 samples where sampling is done by purposive sampling technique. The method used in this research is quantitative, the type of research used is descriptive, the type of data is secondary. Data analysis method used is multiple regression. Data collection techniques using documentation techniques by collecting financial statements manufacturing companies' food and beverage sub-sectors listed on the Indonesia Stock Exchange. The results of this study indicate that Firm Size, Current Ratio, and Total assets have significant and significant effect on profitability (ROE) in food and beverage sub-sector manufacturing companies that are listed on the Indonesia Stock Exchange. Simultaneously Firm Size, Current Ratio, and Total Asset Turnover variables affect Profitability (ROE). Partially the Current Ratio and Total Asset Turnover variables have a positive and significant influence on Profitability (ROE), while the Firm Size has no influence and is significant on Profitability (ROE). The coefficient of determination test results showed a value of 63.7% of the variation in profitability (ROE) which means that profitability can be explained by the variable Current Ratio, Debt to Equity Ratio and Total Asset Turnover